18 No association between tendon-related genes and performance in elite european caucasian marathon runners. (20th December 2017) - Stebbings, GK; Herbert, AJ; Brazier, J; Lockey, SJ; Erskine, RM; Day, SH; Williams, AG
Abstract : Tendons adapt to load under normal physiological conditions, however, under extreme loading conditions, such as those experienced by elite endurance athletes, incomplete adaptation may occur and cause injury. The prevalence of tendinopathies in elite endurance athletes is approximately 50%, thus variability exists in an athlete's tolerance to extreme loading. A number of intrinsic and extrinsic factors contribute to modulating injury risk, some of which are modifiable and others, such as genetic variants, are non-modifiable. It was hypothesised that elite marathon runners would possess a genotype associated with enhanced tendon function, and thus protective against tendinopathy. Here, we compared the genotype frequencies of six genetic variants (COL1A1 rs1800012, VEGFA rs699947, TIMP2 rs4789932, MMP3 rs591058, MMP3 rs650108, MMP3 rs679620), previously associated with tendinopathy, in elite (men <2 hour 30 min, n=109, women <3 hour 00 min, n=99) and sub-elite (men 2 hour 30 min-2 h 45 min, n=189; women 3 hour 00 min-3 h 15 min, n=71) marathon runners with those of a non-athletic control group (n=564). Genotype associations with marathon personal best time in the athlete group were also investigated. All participants provided either a whole blood, saliva or buccal cell sample, from which DNA was isolated, and genotyped for all six variants using real-time PCR. Genotype frequency differed between athletes and controls for TIMP2 rs4789932 (TT=17%, CT=51%, CC=32% vs TT=22%, CT=42%, CC=36%, respectively; χ2=8.135, p=0.017) only. However, there was no clear difference in allele frequencies between groups for TIMP2 rs4789932. MMP3 rs650108 genotype frequency differed between female elite and sub-elite athletes (χ2=11.913, p=0.003) only and, as hypothesised, it was the 'risk' A-allele that was ~10% less frequent in the elite, than sub-elite athletes. Following combination of all genotype data into a total genotype score, no differences in score between athletes and controls were observed (t=2.93, p=0.769). Similarly, no associations between total genotype score and marathon personal best time in male and female runners were observed (r≤0.066, p≥0.394). The results suggest elite marathon runners do not possess a genotype protective against tendinopathy, at least for the tendon-related genetic variants we investigated.